1995
DOI: 10.1016/0954-6111(95)90210-4
|View full text |Cite
|
Sign up to set email alerts
|

Bronchial hyperreactivity in patients with endobronchial tuberculosis

Abstract: Some patients with endobronchial tuberculosis (EBTB) have wheeze on physical examination and normal chest PA, which mimic bronchial asthma. Non-specific bronchial challenge tests have been used to confirm the presence of bronchial hyperreactivity, which is a hallmark of bronchial asthma. To evaluate the effect of endobronchial tuberculous inflammation on bronchial responsiveness to histamine, the provocation concentrations of histamine required to reduce FEV1 by 20% of the pre-challenge baseline (PC20) were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…[8][9][10][11] It has been shown that EBTB may be misdiagnosed as bronchial asthma as it causes wheezing. 12,13 Approximately 24% of the studied patients who had this sign had been mistakenly treated for bronchial asthma for long periods before diagnosis. Radiological workup in 15% of the patients showed thoracic mass lesions in their CT scans, but no invasive procedures were performed until active lung tuberculosis was ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11] It has been shown that EBTB may be misdiagnosed as bronchial asthma as it causes wheezing. 12,13 Approximately 24% of the studied patients who had this sign had been mistakenly treated for bronchial asthma for long periods before diagnosis. Radiological workup in 15% of the patients showed thoracic mass lesions in their CT scans, but no invasive procedures were performed until active lung tuberculosis was ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Exercise challenge and histamine challenges identify different pathways in the airways (31). Although tuberculosis is prevalent both in the Transkei and in Cape Town in the Xhosa population, individuals with endobronchial tuberculosis do not have significantly increased BHR (32).…”
Section: Discussionmentioning
confidence: 99%
“…The bronchostenosis is mainly determined by the extent of disease progression and closely related to the formation of granulation tissue [7,8]. Once fibrostenosis already develops or extensive granulation tissue appears, remarkable bronchostenosis is inevitable despite of efficacious anti-tuberculosis chemotherapy [9-11]. The incidence rate of broncho stenosis may reach up to 68% in initial 4 to 6 months of the disease and rises further with the course of disease elongating [12].…”
Section: Introductionmentioning
confidence: 99%